2021
DOI: 10.3390/molecules26051223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Surface Treatment Methods on Bond Strength of Dental Ceramics to Dental Hard Tissues: A Systematic Review

Abstract: For long-term successful use of ceramic materials in dental procedures, it is necessary to ensure reliable bonding of restorations to dental substrates. This can be achieved by the application of a proper luting cement and through additional surface conditioning. The present systematic review summarizes the most up-to-date evidence on the use of different surface modification methods to enhance the bond strength of dental ceramics to the hard tissues of the teeth. The authors of the review searched the Web of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…The bond strength among restorative materials and dental tissues must be effective at the interface of the restored cavity, mimicking the mechanical properties of lost mineralized tissues and limiting marginal leakage and cusp deflection [ 19 , 20 ]. Morphology, function and esthetics must also be replicated [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The bond strength among restorative materials and dental tissues must be effective at the interface of the restored cavity, mimicking the mechanical properties of lost mineralized tissues and limiting marginal leakage and cusp deflection [ 19 , 20 ]. Morphology, function and esthetics must also be replicated [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors that could further influence fracture resistance are the design of the preparation, framework design, and surface treatments of fixed dental prosthesis [24][25][26]. A study demonstrated that the highest fracture resistance values were observed in the case of the butterfly wings design followed by inlay and box designs [27].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple steps are required to promote adequate bonding between LDC and methacrylate-based materials, such as adhesives or resin-based cements [4,5]. Ceramic surface treatments, such as priming in addition to using a type of luting cement, can influence resin-ceramic bond strength (adhesion) [6,7]. LDC is one of the most used glass-ceramic materials, which can be supplied in a fully or partly crystallized form, which requires crystallization (firing) or heat-pressing.…”
Section: Introductionmentioning
confidence: 99%